Hypopigmented mycosis fungoides in childhood and adolescence: a long‐term retrospective study. (16th October 2013) - Castano, Ekaterina; Glick, Sharon; Wolgast, Lucia; Naeem, Rizwan; Sunkara, Jaya; Elston, Dirk; Jacobson, Mark
<x xml:space="preserve">Abstract</x> Patients with hypopigmented mycosis fungoides (HMF) present at a younger age than those with classic MF. Our goal was to describe the clinical presentation, histopathologic features and long‐term outcome in patients who developed HMF before the age of 21. It was observed that among 69 pediatric patients diagnosed with MF between 1992 and 2010, 50 had HMF. Thirty‐five patients had clinical follow‐up. There were 37 males and 32 females with a mean age of 13.6 years. Most patients were African American or Hispanic and presented with multiple hypopigmented patches. All biopsies showed epidermotropism of T‐lymphocytes, whereas fibroplasia and lichenoid infiltrate were variable. All specimens tested were CD8+. Treatment modalities included topical steroids, narrow band ultraviolet B and psoralen and ultraviolet A. HMF patients were followed for <1–12 years. Most children responded to treatment, but recurrence rates were high. One patient progressed to plaque/tumor stage. Others did not progress; however, many were lost to follow‐up. We present a large cohort of children with HMF and report on the features of disease and progression. A major difference in histology of HMF was lack of fibroplasia and lichenoid infiltrate, probably because of presentation in the early patch stage. Most patients have a waxing‐and‐waning course and relapse after discontinuation of therapy, requiring repetitive treatment.